Spectroelectrochemistry of pyrrole oligomers in the presence of acrylamide - Saraç, A Sezai; Sönmez, Gürsel (Wiley, 2002)
AbstractSoluble pyrrole oligomers were characterized during electropolymerization of pyrrole in the presence of acrylamide (in acetonitrile) which stabilizes radical cations of pyrrole allowing the reaction to be followed by spectroscopic and spectroelectrochemical means. The role of the applied electrical conditions and the effect of the presence of acrylamide on the formation of pyrrole oligomers in solution, and on the resulting polymer on an electrode surface (both Pt and indium tin oxide), were investigated. The soluble and insoluble products were characterized using UV‐visible and FTIR spectroscopy, cyclic voltammetry and a four‐point probe technique. Polypyrrole and poly(pyrrole–acrylamide) free‐standing films had conductivity values of about 90 and 1 S cm−1, respectively. Spectroscopic, cyclovoltammetric and conductivity results support the incorporation of acrylamide into intermediate species that may have useful application in industry.© 2002 Society of Chemical Industry